Analysis of the Liberal and Republican Positions on the Justifications of the Individual and the Common Good Respectively and How These Influence Education and Political Participation - Rodriguez Cardenas, Frank E. (2024)
The present study aims to explore the essential foundations of both liberalism and republicanism, starting from individual freedom and the common good, respectively, and focusing on the fundamental concept of liberty. To achieve this, the concepts of private property, non-interventionism, and state neutrality in liberalism, and community, social purpose, and the public sphere in republicanism, derived from the aforementioned terms, will be analyzed. The objective of this research is to evaluate the practical feasibility of both ideological currents and consider the possibility of a synthesis between them. Hence, the guiding question will be: which of the two is more feasible in practical life, or if there can be a synthesis between them? In response to this question, it is argued that liberalism is the most feasible and viable stance, as republicanism is contradictory in its principles and modes of operation. This analysis seeks to deepen the understanding of the foundations and practical implications of liberalism and republicanism, in order to contribute to the debate on social organization in relation to the principles of individual freedom and the common good.